An Analysis of Speech Acts Used in Pacific Rim 2013 Movie : A Pragmatic Study - Khalish, Muhammad Rayhan; Fitrawati, Fitrawati (Universitas Negeri Padang, 2024)
Speech act is the best way to the speaker delivered a massage that the hearer can understand. In this research the researcher tried to analyze type of speech act and classification of illocutioanary act used in the main character in Pacific Rim Movie. This research uses descriptive qualitative research to examine. The researcher analyzed three parts: all the utterances of the main character, types of speech act, and classification of illocutionary act. The researcher found all the utterances that conducted the types of speech act and the classification of illocutionary act. The study determines the type of speech act and the classification of illocutionary act that are employed in the Pacific Rim movie. As a result, the researcher found 45 representative, 67 directive, 5 commissive, 14 expressive, 0 declarative for classification of illocutionary act, and the most dominant classification of illocutionary act is directive with 67 utterances. In conclusion, the main character utterances contains directive serve as a individuals to express their desires on intentions, typically involving requesting someone to do something, forbidding certain actions, ordering, asking for assistence or information, commanding actions to be taken, suggesting possible courses of action, or advising on a particular course of action.